Mitochondrial DNA and diseases - Sun, Hongzhi; Wang, Xiangdong (Professor of clinical bioinformatics) (Springer, 2017)
The book describes molecular principles and mechanisms by which mitochondrial DNA (mtDNA) can drive the occurrence of diseases and the latest understanding of mtDNA biology. The book explores roles of mtDNA mutation and genetic changes in cancer, with a special focus on lung cancer, and the significance of approach, application, and bioethics of mtDNA sequencing. Authors made a great effort to overview roles of mtDNA signaling pathways, base excision repair, methylation, USP30-mediated regulation, mitochondrial ribosome, autophagy pathways, or ROS-dependent signaling in the pathogenesis, diagnosis, prevention and treatment of diseases. It also demonstrates the importance of basic mitochondrial genetics and the relationship between mutations and disease phenotypes and ageing. This book covers not only the basic information of mtDNA, the relationship of mtDNA and disease, but also mtDNA in stem cell and mitochondria and metabolism etc. The book is written for biological and clinical students and researchers in the field of mtDNA-associated diseases.
Keywords: Mitochondrial DNA.; Mitochondrial DNA -- Abnormalities.; elektronické knihy; electronic books